Development of an automated method for in-house production of sodium 18F-fluoride for injection: process validation as a step toward routine clinical application - Marija Atanasova Lazareva; Maja Chochevska; Katerina Kolevska; Maja Velickovska; Filip Jolevski; Paulina Apostolova; Ana Ugrinska; Emilija Janevik-Ivanovska (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Sodium 18F-fluoride for injection can be easily cyclotron-produced and purified, as a simple inorganic salt, by adsorption/desorption onto an anion-exchange cartridge and then dispensed for clinical use. Since the clinical demand for this radiopharmaceutical is constantly increasing, this study aimed to design and develop a simple, fully automated method for the in-house, rapid, and efficient processing and dispensing of injectable solutions of Sodium 18F-fluoride without the need of a synthesis module and disposable kit, but using only the dispensing unit. Results A new simple method for the efficient routine production of injectable solutions of [18F]NaF was developed through a straightforward modification of the commercial dispenser Clio (Comecer S.p.A., Italy) and without the need of a synthesis module. The full production, processing and dispensing of [18F]NaF were entirely carried out on the same batch using only the dispensing module. Process validation was carried according to GMP guidelines to ensure consistency of [18F]NaF quality with international standards. The final radiopharmaceutical met all quality criteria specified by Ph. Eur. and chemical, radionuclidic and radiochemical impurities were significantly below the required limits. Conclusion A new simple and reliable procedure developed for the preparation and dispensing of injectable [18F]NaF in less than 10 min with a radiochemical yield > 97% (decay corrected) has been successfully developed. Notably, the proposed method also allows the preparation of [18F]NaF using the residual fluorine-18 activity remaining after a [18F]FDG production run, thus making it immediately accessible to patients for further PET imaging investigations.